Effect of Neutral Proteases from Blood Leukocytes on Human Platelets - Bykowska, K; Kaczanowska, J; Karpowicz, M; Stachurska, J; Kopeć, J (Thrombosis and Haemostasis, 1983)
Two highly purified neutral proteases from human leukocytes i.e. elastase-like protease (ELP) and chymotrypsin-like protease (CLP) do not destroy human platelets since no difference was found in 51Cr liberation from control and enzyme-treated platelets. As with pancreatic chymotrypsin (α-CT) ELP does not induce the release of 3H-serotonin while CLP provokes 3H- serotonin secretion, in an enzyme concentration and time dependent fashion. The rate and degree of 3H-serotonin release by CLP is similar to that produced by thrombin. Incubation of platelets at 37° C for 30 min with α-CT or ELP renders them resistant to thrombin-releasing activity. Thrombin did not liberate any additional label from platelets which lost over 60% of serotonin during the preceding incubation with CLP. α-CT and ELP do not aggregate platelets either in the presence or absence of apyrase. CLP does aggregate platelets suspended in Tyrode buffer without apyrase but not in the presence of apyrase (100 mg/1). The action of α-CT, ELP and CLP on washed platelets induces a progressive prolongation of lag phase and a decrease in changes of light transmission during aggregation by thrombin. Similarly to α-CT-treated platelets, those subjected to CLP action aggregate in the presence of human fibrinogen.It is concluded that: (1) neutral proteases possibly contribute to development of defects in platelet function in pathological states associated with liberation of leukocyte content into the circulation, (2) CLP similarly to a-CT, exposes fibrinogen receptors but in contrast to α-CT, CLP aggregates platelets and stimulates serotonin secretion.
Keywords: Neutral leukocytic proteases; Human blood platelets